Postural stability in patients with cystic fibrosis - Prusak, Jarosław; Kurzeja, Piotr; Szurmik, Tomasz; Mrozkowiak, Mirosław; Umławska, Wioleta (Journal of Education, Health and Sport, 2018)
Summary Aim of the study: The aim of the study was to evaluate the postural stability in a group of patients with cystic fibrosis. Material and methods: The study included a group of 44 patients with cystic fibrosis with the analysis of parameters in the age groups under 16 years (mean 10,1 ± 3,6) and over 16 years (mean 23,6 ± 7,3). For stabilometric measurements, a two-plate CQ Stab posturograph and for body posture measurements Posturometr-S was used. Results: The mean value of the SP body balance COP index in the measurement with open eyes was 336,1 ± 123 mm in the younger group and 201,3 ± 47 mm in the older age group. The results differed significantly in the measurement with closed eyes in both age groups, similarily to the other indicators of the balance in the assessment for each planes. The indicators associated with the assessment of COP displacement significantly correlated negatively with the age of the subjects, where for the measurement with eyes closed this relationship was the highest in the group up to 16 years and was r = - 0,90 (p <0,0001) and the size of the chest kyphosis angle ( for the whole group: r = - 0,45, p = 0,002) and some indicators of the pulmonary system. The correlation value for FEV1% pred., for the whole group, was r = 0,41 (p = 0,005). It was observed that with the age of the subjects, the kyphosis angle increased (for the group > 16 years: r = 0,77, p <0,0001). Conclusions: The results of the study show that with age of the cf patients, changes in the spine in the sagittal plane, the parameters related to postural stability of the body may be improved.